Bullying and student burnout: A qualitative case study of a rural Indonesian junior high school - Mukhlis, Mukhlis; Yustika, Saidah (STAI Auliaurrasyidin Tembilahan, 2025)
Bullying represents a critical challenge in educational settings, yet its specific role in fostering student burnout within rural Indonesian contexts remains insufficiently explored. This qualitative case study addresses this gap by investigating the nexus between bullying and student burnout at SMP Negeri 1 Bukit Malintang. Data were collected through semi-structured interviews with seven school staff members, 25 hours of non-participant observation, and document analysis. Thematic analysis revealed three central findings. First, students who lacked strong peer networks were identified as vulnerable targets for both physical and psychological bullying. Second, the experience of victimization manifested directly in the core symptoms of student burnout: emotional exhaustion, cynicism toward school, and a reduced sense of academic accomplishment. Third, the school's institutional response was characterized by reactive, teacher-centered interventions, highlighting a significant gap in proactive and systemic support strategies. The study concludes that bullying acts as a chronic psychosocial stressor that catalyzes student burnout, a process intensified by local contextual factors such as parental migration. These findings underscore the urgent need for educational policies and interventions that move beyond punitive measures to implement holistic, community-engaged programs designed to build inclusive environments and robust support.